Millard–Gubler Syndrome due to Parenchymal Neuro-Behcet’s Syndrome Lesion: A Rare Case Report - Bünyamin Tosunoğlu; Burcu Gökçe Çokal; Hafize Nalan Güneş; Tahir Kurtuluş Yoldaş (Acta Neurologica Taiwanica)
Behcet's disease; it is a vascular-inflammatory chronic recurrent disease that can affect many systems in the body. Millard–Gubler syndrome is one of the brainstem syndromes that occur due to lesions involving the ventral part of the caudal pons. We wanted to present a case of Millard–Gubler syndrome, which developed due to Behçet’s syndrome lesion in the pons ventral region in a patient who presented with limitation of outward gaze on the left, inability to close the left eye completely, inability to completely wrinkle the left side of the forehead, and loss of contralateral muscle strength.